Polymicrobial Infections and Biofilms: Clinical Significance and Eradication Strategies - V T Anju; Siddhardha Busi; Madangchanok Imchen; Ranjith Kumavath; Mahima S. Mohan; Simi Asma Salim; Pattnaik Subhaswaraj; Madhu Dyavaiah (MDPI AG, 2022)
Biofilms are population of cells growing in a coordinated manner and exhibiting resistance towards hostile environments. The infections associated with biofilms are difficult to control owing to the chronicity of infections and the emergence of antibiotic resistance. Most microbial infections are contributed by polymicrobial or mixed species interactions, such as those observed in chronic wound infections, otitis media, dental caries, and cystic fibrosis. This review focuses on the polymicrobial interactions among bacterial-bacterial, bacterial-fungal, and fungal-fungal aggregations based on in vitro and in vivo models and different therapeutic interventions available for polymicrobial biofilms. Deciphering the mechanisms of polymicrobial interactions and microbial diversity in chronic infections is very helpful in anti-microbial research. Together, we have discussed the role of metagenomic approaches in studying polymicrobial biofilms. The outstanding progress made in polymicrobial research, especially the model systems and application of metagenomics for detecting, preventing, and controlling infections, are reviewed.